ESG performance, green banking disclosure and firm value: Empirical evidence in Indonesia - Umbing, Golda Belladonna; Yuniati, Ade; Wardani, Sabila Kusuma (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2024)
This research aims to examine the effect of ESG performance and green banking diclosure on firm value. The research was conducted on conventional banking companies listed on the Indonesia Stock Exchange from 2021-2022. The independent variables used in this research are green banking performance and ESG performance. The dependent variable used in this research is company value. The control variables used are company size and audit quality. The data used in this research was obtained through the ESGI Dataset. Determination of the regression model using panel data was carried out through the Chow test and Hausman test. The results shows that the environment score variable has a positive effect on company value, while the other three variables, namely social score, governance score and green banking disclosure have no effect on company value. This implies that investors in the banking sector have not fully focused on the ESG and green banking disclosure dimensions in decision making.